Elongatoolithid eggs containing oviraptorid (Theropoda, Oviraptorosauria) embryos from the Upper Cretaceous of Southern China. Issue 1 (December 2016) - Wang, Shuo; Zhang, Shukang; Sullivan, Corwin; Xu, Xing
Abstract Background Oviraptorids, like many other dinosaurs, clearly had a complex pattern of skeletal growth involving numerous morphological changes. However, many ontogenetic skeletal changes in oviraptorids were previously unclear due to the lack of well preserved specimens that represent very young developmental stages. Results Here we report three elongatoolithid dinosaur eggs from the Upper Cretaceous Nanxiong Formation of Nankang District, Ganzhou City, Jiangxi Province, China that containin ovo embryonic skeletons. The eggs themselves show diagnostic features of the oofamily Elongatoolithidae, whereas the embryos are identified as taxonomically indeterminate oviraptorids. The three new specimens display pathological eggshell features, including double-layered and multilayered cones in the columnar layer, which probably result from high levels of pathogenic trace elements in the environment. Nevertheless, the skeletons of the preserved embryos exhibit no structural or histological abnormalities. Comparisons between the new embryos and other oviraptorid specimens reveal 20 osteological features that appear to change substantially during ontogeny in oviraptorids. For example, the dorsoventral height of the skull increases more rapidly than the anteroposterior length during oviraptorid ontogeny, and the initially paired nasals fuse at an early stage, presumably facilitating growth of a crest. Conclusions The new specimens represent the first known oviraptorid embryos associated with pathological eggshells. The absence of structural and histological abnormalities indicates the environmental factor that led to the eggshell pathologies did not affect the skeletal development of the oviraptorids themselves. As in tyrannosaurids, but in contrast to the situation in other maniraptorans, the oviraptorid skull becomes proportionally dorsoventrally deeper during ontogeny. Although oviraptorids and therizinosauroids occupy broadly the same grade of maniraptoran evolution, the embryonic ossification patterns of the vertebral column and furcular hypocleidium appear to differ significantly between the two clades. The limb proportions of juvenile oviraptorids indicate that they were bipedal, like adults. Oviraptorids may have differed greatly from therizinosauroids in their growth trajectories and locomotor modes during early post-hatching ontogeny, essentially occupying a different ecological niche.